Stress distribution in an elastic body with a periodically curved row of fibers - Akbarov, SD; Kosker, R; Ucan, Y (SPRINGER, 2004)
Within the framework of a piecewise homogeneous body model, with the use of exact three-dimensional equations of elasticity theory for anisotropic bodies, a method is developed for investigating the stress distribution in an infinite elastic matrix containing a periodically curved row of cophasal fibers. It is assumed that fiber materials are the same and fiber midlines lie in the same plane. The self-balanced stresses arising in the interphase in uniaxial loading the composite along the fibers are investigated. The influences of problem parameters on these stresses are analyzed. The corresponding numerical results are presented.
Keywords: unidirectional fibrous composite; curved fibers; row of fibers; self-balanced stresses; COMPOSITES; MECHANICS; Materials Science; Polymer Science